Design of a Silicon Carbide Chemical Vapor Deposition Reactor Cleaning Process Using Chlorine Trifluoride Gas Accounting for Exothermic Reaction Heat. (29th October 2020) - Hayashi, Masaya; Mamyouda, Takumi; Habuka, Hitoshi; Ishiguro, Akio; Ishii, Shigeaki; Daigo, Yoshiaki; Ito, Hideki; Mizushima, Ichiro; Takahashi, Yoshinao
Abstract : A silicon carbide chemical vapor deposition reactor cleaning process was designed by managing and utilizing the temperature increase due to the exothermic reaction heat produced by the chemical reaction between chlorine trifluoride gas and a particle-type polycrystalline silicon carbide layer. The main issues were (i) the initial susceptor temperature, (ii) the exothermic reaction heat, and (iii) the heat transport from the susceptor surface for reducing the peeling of the susceptor coating film. The important parameter was the initial susceptor temperature for performing the moderate etching of the silicon carbide layer and the local etching at the contact point between the silicon carbide particles and the susceptor surface. The 30- μ m-thick particle-type polycrystalline silicon carbide layer could be detached and cleaned in two minutes.